Prevalence and risk factors for coronary artery disease in patients on chronic hemodialysis - Ljubičič, Jelena; Pesic, Andrej; Marinkovic , Nikola; Kravljaca, Milica (Medicinski podmladak, 2021)
Introduction: Cardiovascular diseases (CVD) represent the leading cause of morbidity and mortality (46-60%) among patients with chronic kidney disease (CKD). Three methods are used for kidney function replacement in patients with end-stage renal disease: hemodialysis, pertioneal dialysis and kidney transplantation. About 40% of the dialysis population develop coronary artery disease (CAD) due to chronic metabolic and inflammatory disorders. Risk factors for developing CAD in this group of patients include chronic anemia, secondary hyperparathyroidism, chronic inflammation, insulin resistance and volume overload. Aim: To determine the impact of metabolic and inflammatory disorders in developing CAD in patients with CKD that are chronically treated with hemodialysis. Material and Methods: This case-control study included 115 patients with end-stage renal disease that were treated in Hemodialysis ward, Clinic for Nephrology, University Clinical Centre of Serbia. Data were collected for the period from January 2015. to December 2020. Elective coronarography was used to determine the presence and the characteristics of CAD. We also analyzed patient’s laboratory findings, their demographic and clinical characteristics, as well as primary renal disease that led to the development of CKD in these patients. Additional parameters used in this study included the presence of Diabetes mellitus and duration of hemodialysis. Results: CAD was diagnosed in 19 out of 115 patients (16.5%). Patients with CAD had a significantly higher levels of serum calcium (2.3 to 2.2 mmol/L) (p=0.039), while other laboratory parameters did not show significant correlation. Most of the patients with CAD were male (16 of 19 patients, 84.3%, p=0.01), while 31.6% (6 of 19 patients) with CAD were diagnosed with Diabetes mellitus (p=0.009). Conclusion: The presence of Diabetes mellitus, higher calcium level, as well as male gender signicifantly increase the risk of developing CAD in patients chronically treated with hemodialysis. Keywords: Chronic kidney disease, hemodyalisis, coronary artery disease, Diabetes mellitus